Narrow-Band Imaging Magnifying Endoscopy versus Lugol Chromoendoscopy with Pink-Color Sign Assessment in the Diagnosis of Superficial Esophageal Squamous Neoplasms: A Randomised Noninferiority Trial - Kenichi Goda; Akira Dobashi; Noboru Yoshimura; Masayuki Kato; Hiroyuki Aihara; Kazuki Sumiyama; Hirobumi Toyoizumi; Tomohiro Kato; Masahiro Ikegami; Hisao Tajiri (Gastroenterology Research and Practice)
Previous studies have shown the high diagnostic accuracy of narrow-band imaging magnifying endoscopy (NBI-ME) and Lugol chromoendoscopy with pink-color sign assessment (LCE-PS) for superficial esophageal squamous cell carcinoma (SESCC). However, there has been no controlled trial comparing these two diagnostic techniques. We conducted a randomized noninferiority trial to compare the diagnostic accuracy of NBI-ME and LCE-PS. We recruited patients with, or with a history of, squamous cell carcinoma in the head and neck region or in the esophagus. They were randomly assigned to either NBI-ME or LCE-PS. When lesions > 5 mm in diameter were found as brownish areas on NBI or as Lugol-voiding lesions (LVL), they were evaluated to determine whether they are SESCC on the basis of the findings of NBI-ME or PS in the LVL. NBI-ME and LCE-PS were completed in 147 patients each. There was no significant difference in all diagnostic values between the two techniques. Compared with LCE-PS, NBI-ME showed a significantly shorter examination time but a larger number of misdiagnosed lesions especially in patients with many irregularly shaped multiform LVLs. Compared with LCE-PS, NBI-ME might be similarly accurate and less invasive, but less reliable in patients with many LVLs, in the diagnosis of SESCC.